The Performance Of Healthcare Providers Concerning Infection Control Measures In Primary Healthcare Facilities In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background: Health care–associated infections (HAI) and antimicrobial resistance (AMR) remain a major challenge to patient safety worldwide, leading to adverse patient outcomes, increased health care costs, and additional burden on the health care system. Healthcare providers (HCPs) can perform basic infection prevention measures to prevent infection. Proper safety measures are intended to shield patients from possible cross-infection as well as to shield employees from hazards brought on by contact with bodily fluids like blood. The body of knowledge regarding clinical infection control procedures is always expanding and evolving.  Therefore,The study aimed: To assess HCPs’ performance regarding infection control precautions in primary health care centers.Method: A descriptive analytical design was used. A total of 379 healthcare providers (HCPs) were engaged from January to May 2024, at selected primary health care centers in Kang of Saudi Arabia (KSA). Tools of data collection: three tools were used to collect data: a structured self- administrated HCPs' questionnaire, observational check list, and environmental assessment checklist.Results: According to the findings, 58.6% of the nurses in the study practiced inept infection control measures, while 44.6% of them had mediocre overall understanding. Additionally, there was a highly significant positive linear association between the practice of nurses and their overall understanding of infection control measures in primary health care centers (r = 0.317, and p = 0.000).Conclusion: According to the findings of the current study, over one-third of the nurses had an average overall knowledge score, and over half of them practiced infection control procedures incompetently. It was shown that there was a highly statistically significant positive linear link between the practice of nurses and their overall knowledge of infection control measures in primary health care facilities. In order to address the lack of information and to update nursing practice regarding standard precautions for infection control, an obligatory regular base educational program must be designed.